Childhood Trauma May Explain Gains in Relationship Satisfaction After Integrative Couple Therapy - Stahl, Benjamin; Sittig, Lea; Milek, Anne; Gehrmann, Florian-Hendrik; Lussana, Marcello; Rizzonelli, Marta; Staudt, Pascal; Kim, Jin Hyun (Taylor & Francis, 2025)
Childhood trauma may affect adult romantic relationships by evoking formerly adaptive, now possibly harmful compensatory strategies in interpersonal conflicts. The present waiting-list controlled predictor-of-efficacy study explores the influence of childhood trauma on change in relationship satisfaction after intensive couple therapy (www.who.int registry identifier: NCT04830553). Fifteen couples—overall 30 individuals with comparatively diverse backgrounds—went through an initial waiting period and subsequent outpatient treatment. Each stage lasted 5 weeks. The intervention involved weekly 2-hour sessions of integrative couple therapy. Testing included the Childhood Trauma Questionnaire (CTQ) as a predictor and the Couples Satisfaction Index (CSI) as a primary outcome before (T0) and immediately after the waiting period (T1) and treatment phase (T2). A repeated-measures analysis of covariance (n = 30) accounting for CSI baseline (T0) revealed a significant interaction (p = .012) between CTQ scores and change in CSI performance (T2–T1). The effect size of this interaction was large (η2 = 0.387). Higher CTQ scores (i.e., more early-life exposure to abuse or neglect) reflected greater CSI gains (i.e., more treatment benefit). As expected, no significant change in CSI performance occurred during the waiting period (T1–T0). The current work identifies severity of childhood trauma as a potential key predictor of progress in couple therapy. Clients, practitioners, and researchers alike are encouraged not to prematurely judge history of childhood trauma as an unfavorable sign for the outcome of couple therapy, but to cautiously assume a strong capacity for growth in romantic relationships for adults with early-life exposure to abuse or neglect.
Keywords: parisuhde; pariterapia; lapsuus; traumat